Doğal elyaf takviyeli polipropilen malzemenin kimyasal köpürtme ajanı takviyesi ile elde edilen kompozitin mekanik, termal ve morfolojik özelliklerinin incelenmesi - Aslan, Yeşim (My University, 2022)
Bu çalışmada doğal elyaf takviyeli polipropilen (PP) malzemenin içerisine %1-2-3 oranlarında kimyasal köpürtme ajanı takviyesi yapılmıştır. Enjeksiyon makinesinde uygun kalıplarda enjeksiyon yöntemiyle kalıplanarak standart deney numuneleri elde edilmiştir. Elde edilen bu deney numunelerine çekme, darbe, sertlik, MFI, HDT-Vicat, aşınma, sürtünme, su emme, yoğunluk gibi mekanik, tribolojik ve ısısal testler uygulanmıştır. Bu deneylerin yanı sıra baloncukların yapıdaki dağılımlarının incelenmesi maksadıyla SEM incelemeleri yapılmıştır. Yapılmış olan tüm bu deney neticelerinin incelenmesiyle doğal elyaf takviyeli polipropilen (PP)’e katılan baloncukların, elde edilen doğal elyaf takviyeli plastik kompozitinin mekanik, tribolojik, ısısal ve mikroyapısal özelliklerini önemli ölçüde değiştirdiği tespit edilmiştir. Çalışmamızın ilk bölümünde malzemeler, doğal elyaf takviyeli plastik kompozitler hakkında verilmiş olup çalışma konumuzla ilgili yapılan çalışmalar ve sonuçları sunulmuştur. İkinci bölümde araştırmada kullanılan malzemeler ve numunelerin elde edilmesi anlatılmıştır. Bu bölümde numuneler üzerinde uygulanan testler hakkında da bilgi verilmiştir. Üçüncü bölümde ise yapılan deneyler sonrası elde edilen sonuçlar ve bu sonuçlara ait grafikler sunulmuştur. Son bölümde ise deney sonuçlarının yorumlanmasına yer verilmiştir.

The automotive industry is among the priority technology areas of our country, and the reduction of vehicle weight and fuel consumption and thus CO2 emissions without compromising safety criteria are among the priority research areas. For this reason, R&D studies on increasing the use of polymer-based materials in the automotive industry are of great importance. In order to produce “high strength and weight reduction parts” in plastic molding technologies, advanced technologies that focus on cost reduction and efficiency are being implemented rapidly. The chemical foaming process, which provides many advantages such as reducing the consumption of plastic material used, reducing the total molding cycle time, using less tonnage injection molding machines, and thus reducing the energy costs, is one of the innovative technologies that have been implemented since a very recent time. In this study, chemical foaming agent were be reinforced at the rate of 1-2-3% in natural fiber-reinforced recycled composite polypropylene raw material. The samples obtained in the injection machine was be molded in the sizes and shapes in accordance with the standards. Tensile, hardness, impact and three points bending tests would be done. Not only mechanical proporties, but also physical proporties is investigated. Such as; Water absorption test, melt flow index test (MFI), density, Vicat softening temperature, heat deflection temperature (HDT), water absorption, %water absorption, abrasive test would done. By examining the test results, the mechanical, and morphological properties of natural fiber reinforced polypropylene materials at different chemical agent percentages were examined. With increasing the amount of foaming agent, mechanical properties decreased. Optimum yield can be obtained from the results by investigating property changes. The morphology of the microcellular hemp fibre composites were examined using scanning electron microscopy (SEM) to observed cell morphology cell size, shape, and distribution of cells account for physical properties behavior.
Keywords: Engineering; kalıp chemical blowing agent; kimyasal köpürtme teknolojisi; Metallurgy; Metalurji; mold; Mühendislik; plastic injection; plastik enjeksiyon